Crystal Structure of the Yeast Metacaspase Yca1 - Wong, Ada Hang-Heng (American Society for Biochemistry and Molecular Biology, 2012)
Yca1, the only metacaspase in Saccharomyces cerevisiae, is thought to be a clan CD cysteine protease that includes the caspase subfamily. Although yeast is a single cell eukaryote, it can undergo a cell death process reminiscent of apoptosis. Yca1 has been reported to play an important role in the regulation of such apoptotic process. However, the structure and functional mechanism of Yca1 remain largely enigmatic. In this study, we report the crystal structure of the Yca1 metacaspase at 1.7 Å resolution, confirming a caspase-like fold. In sharp contrast to canonical caspases, however, Yca1 exists as a monomer both in solution and in the crystals. Canonical caspase contains six β-strands, with strand β6 pairing up with β6 of another caspase molecule to form a homodimerization interface. In Yca1, an extra pair of antiparallel β-strands forms a continuous β-sheet with the six caspase-common β-strands, blocking potential dimerization. Yca1 was reported to undergo autocatalytic processing in yeast; overexpression in bacteria also led to autoprocessing of Yca1 into two fragments. Unexpectedly, we found that both the autocatalytic processing and the proteolytic activity of Yca1 are greatly facilitated by the presence of calcium (Ca(2+)), but not other divalent cations. Our structural and biochemical characterization identifies Yca1 as a Ca(2+)-activated cysteine protease that may cleave specific substrates during stress response in yeast.